2011
DOI: 10.1136/ard.2011.151902
|View full text |Cite|
|
Sign up to set email alerts
|

Delays in assessment of patients with rheumatoid arthritis: variations across Europe

Abstract: This research highlights the contribution of patients, professionals and health systems to treatment delay for patients with RA in Europe. Although some centres have strengths in minimising certain types of delay, interventions are required in all centres to ensure timely treatment for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 14 publications
6
112
1
7
Order By: Relevance
“…Recent research, however, shows a median delay from symptom onset to treatment initiation ranging from 16 to 38 weeks in different countries (8,9). Raza et al, showed that delay in referral to a rheumatologist importantly contributed to the overall treatment delay in early RA (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research, however, shows a median delay from symptom onset to treatment initiation ranging from 16 to 38 weeks in different countries (8,9). Raza et al, showed that delay in referral to a rheumatologist importantly contributed to the overall treatment delay in early RA (9).…”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, the survey results are an improvement upon a previous Midlands audit on RA in 2008, when 84.5% of patients were seen within three months. 14 In the patients who presented after the three-month target, the delay was mostly before referral, similar to previous data, which suggests that the delay in presentation to primary care is the main reason why patients with RA are seen late by rheumatologists.…”
Section: Resultsmentioning
confidence: 76%
“…The first three months after symptom onset are an important therapeutic window for RA 12 and disease duration at the time of DMARD initiation has been shown to be the primary predictor of response to DMARD treatment. 13 The survey shows that most patients (95.6%) were assessed by a rheumatologist within three ACPA ϭ anti-citrullinated peptide antibody; CRP ϭ C-reactive protein; DAS-28 ϭ disease activity score 28; DMARD ϭ disease-modifying antirheumatic drug; EIAC ϭ early inflammatory arthritis clinic; MDT ϭ multidisciplinary team; RA = rheumatoid arthritis; RF ϭ rheumatoid factor every three months.…”
Section: Discussionmentioning
confidence: 99%
“…Results are summarized in Table 1. In summary, strategies studied to reduce waiting times for a rheumatological appointment were based on implementation of a unspecifi c triage system [7], a consultancy program [12] and an immediate access clinic (IAC) [6] or systematic search for reasons responsible for delayed consultations [13][14][15]. Out of these the rapid access service [6], early arthritis clinic [16], triage of referrals with use of referral forms [7] and educational programs for primary care physicians and health professionals [12] were shown to be effective interventions resulting in reduction of referral delays.…”
Section: Literature Searchmentioning
confidence: 99%